2019
DOI: 10.1542/peds.2019-1187
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Suicidal Behaviors Among High School Students in the United States: 1991–2017

Abstract: OBJECTIVES: To determine if racial and ethnic subgroups of adolescents are at high risk for engagement in suicidal behaviors.METHODS: Using the nationally representative school-based Youth Risk Behavior Survey from the years 1991 to 2017, we conducted logistic regression analyses to examine trends by different racial and ethnic groups, with each suicide indicator serving as a dichotomous outcome. Participants included 198 540 high school students.RESULTS: Across all sex and race and ethnic groups, there were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
232
10
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 297 publications
(256 citation statements)
references
References 49 publications
(45 reference statements)
11
232
10
3
Order By: Relevance
“…Accordingly, there is need to consider the multiple minority stressors that these SMY of color might face. Future research should assess how these experiences might impact any increased suicidal thoughts and behaviors among SMY of color, especially given recent research that indicates increasing rates of attempted suicide among Black adolescents (Lindsey, Sheftall, Xiao, & Joe, 2019). Finally, youth within the profiles representing SMY (by different combinations of nonexclusive heterosexual identity and behavior) more frequently endorsed experiencing bullying and feelings of sadness/hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is need to consider the multiple minority stressors that these SMY of color might face. Future research should assess how these experiences might impact any increased suicidal thoughts and behaviors among SMY of color, especially given recent research that indicates increasing rates of attempted suicide among Black adolescents (Lindsey, Sheftall, Xiao, & Joe, 2019). Finally, youth within the profiles representing SMY (by different combinations of nonexclusive heterosexual identity and behavior) more frequently endorsed experiencing bullying and feelings of sadness/hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…12 One hypothesis for protective factors is that external attributional orientation (eg, blaming others or "the system" for difficulties) among blacks may have buffered this group from internalizing blame related to psychological stressors. 12 The increased rate of suicide by black adolescents, particularly girls, and the findings of Lindsey et al 5 of increases in the rate of black adolescent suicide attempts (accelerating among girls) suggest that protective factors have diminished. For example, the attributional orientation of black adolescents may have shifted toward an internal orientation, thus leading to an increase in suicide risk factors, particularly depression.…”
mentioning
confidence: 99%
“…In this issue of Pediatrics, Lindsey et al 5 examine the results of the Youth Risk Behavior Survey from 1991 to 2017 with regard to trends by sex and racial or ethnic subgroups. The Youth Risk Behavior Survey is a nationally representative, self-report survey of high school students that asked about suicidality over the previous 12 months.…”
mentioning
confidence: 99%
“…Recent research examining trends of suicidal behaviors among adolescents of different racial and ethnic groups in the United States has shown an increase in suicide attempts among black youth with a significant increase in injury by attempts among black males ( Lindsey et al., 2019 , Pediatrics). The rise in the number of suicidal attempts is thought to be related to mental health and socio etiologic factors incommensurately experienced by black youth, including poverty and racial discrimination ( Lindsey et al., 2019 , Pediatrics). Stress-related to the aforesaid ethnicity groups including victimization is expected to account for their increased risk of suicidality (Thoma et al., 2019; Pediatrics).…”
Section: Psychosocial Risk Factors Of Suicidal Behavior In Adolescentmentioning
confidence: 99%
“…Research has found substantial gender and racial/ethnic differences in suicide risk factors among youth underscoring the need for this ( Lee and Wong, 2020 ). Recommendations for interventions tailored to the black community include efforts to increase access to mental health care by reducing stigma and increasing help-seeking behavior ( Lindsey et al., 2019 ). Researchers examining risk and protective factors related to adolescent suicide attempts recommend psychotherapy aimed at treating persistent depression and increasing productive coping skills ( Mirkovic et al., 2020 ).…”
Section: Current and Future Strategies For Prevention Intervention mentioning
confidence: 99%